2017
DOI: 10.1016/j.jallcom.2016.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, microstructure and mechanical properties of W NiTi composites

Abstract: a b s t r a c tNew two-phase tungsten-based composites containing 88 wt% tungsten powders and 12 wt% nearly equiatomic NiTi alloy deforming by martensite variant detwinning were fabricated by infiltration and hot pressing in this study. 53 Nb 5 composite exhibited a double-yielding phenomenon under compression with an ultimate compressive strength of 3820 MPa and a deformation of 50.4%. In-situ synchrotron high-energy Xray diffraction measurements revealed the first yielding was caused by the martensite reor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The second method is the introduction of strengthening phases into NiTi SMA matrix composites (SMACs). Soft/hard dual-phase composites have received a lot of attention recently because of their excellent mechanical properties and high damping capacities. For instance, it was reported that Ti 3 Sn showed excellent damping performance and desirable mechanical properties at a wide temperature range. Zhang et al observed that dense NiTi/Ti 3 Sn composites exhibited a high compressive strength of 3.0 GPa and a fracture strain of 33%. This excellent performance was attributed to lattice strain matching and the large interfacial area between the brittle Ti 3 Sn phase and the ductile NiTi phase in the composite.…”
Section: Introductionmentioning
confidence: 99%
“…The second method is the introduction of strengthening phases into NiTi SMA matrix composites (SMACs). Soft/hard dual-phase composites have received a lot of attention recently because of their excellent mechanical properties and high damping capacities. For instance, it was reported that Ti 3 Sn showed excellent damping performance and desirable mechanical properties at a wide temperature range. Zhang et al observed that dense NiTi/Ti 3 Sn composites exhibited a high compressive strength of 3.0 GPa and a fracture strain of 33%. This excellent performance was attributed to lattice strain matching and the large interfacial area between the brittle Ti 3 Sn phase and the ductile NiTi phase in the composite.…”
Section: Introductionmentioning
confidence: 99%